Tephrochronology in Aotearoa New Zealand. Issue 2 (3rd July 2021) - Hopkins, Jenni L.; Lowe, David J.; Horrocks, Joanna L.
ABSTRACT: Tephra deposits in Aotearoa New Zealand (ANZ) have been studied for >180 years. The now-global discipline of tephrochronology, which has some developmental roots in ANZ, forms the basis of a powerful chronostratigraphic correlational tool and age-equivalent dating method for geological, volcanological, palaeoenvironmental, and archaeological research in ANZ. Its utility is founded on the key principle that tephras or cryptotephras provide widespread isochrons in many different environments. In the first part of this article, we summarise the history of tephra studies in ANZ and then describe how tephras have been mapped, characterised, and correlated using field and laboratory-based methods. We document advances in geochemical fingerprinting of glass; tephra/cryptotephra detection and correlation by sediment-core scanning methods (e.g. X-radiography, CT imaging, XRF elemental analysis, magnetic susceptibility); statistical correlation methods; and dating of tephras/cryptotephras. We discuss the advent of ANZ cryptotephra studies (from mid-1970s) and their more-recent growth. The second part comprises examples of applications of tephrochronology in ANZ: climate-event stratigraphy (NZ-INTIMATE project); eruptive-event stratigraphy in the Auckland Volcanic Field; developments in the marine tephra record; advances in identifying, correlating, and dating old (pre-50 ka) tephras and weathered-tephra deposits; forming soils/paleosols on tephras; tephras and archaeology; Kopouatai bog tephrostratigraphy and palaeoenvironments; and volcanic-hazard assessments.